Contemporaneous mobile- and stagnant-lid tectonics on the Hadean Earth - John W. Valley; Tyler B. Blum; Kouki Kitajima; Kei Shimizu; Michael J. Spicuzza; Joseph P. Gonzalez; Noriko T. Kita; Ann M. Bauer; Stephan V. Sobolev; Charitra Jain; Aaron J. Cavosie; Alexander V. Sobolev (Nature, 2026)
Abstract The first billion years of Earth history witnessed the emergence of continental magmatism, oceans and life. Yet, the details of how continents formed remain unknown because of the absence of preserved rocks 1–8 . Two conflicting Hadean models predominate: early onset of subduction and plate tectonics 2–4 , compared with early stagnant-lid and plume processes with delayed (post-Hadean) plate tectonics 5–7 . Here we report trace-element ratios (including Nb–Sc–U–Yb) correlated with age and hafnium and oxygen isotope ratios for Hadean detrital zircons from the Jack Hills (JH), Western Australia, which record unprecedented insights into the timing and setting of early magmatism. More than 70% of Hadean JH detrital zircons have Sc/Yb > 0.1, and 47% have U/Nb > 20, fingerprints for continental-arc and subduction settings. The remainder are ocean-island-like with little evidence for ocean-ridge settings. Hadean JH zircons probably originated from distinct terranes with separate tectonic histories. Subduction-related magmatism in the Hadean, as documented by JH zircons, alternated with periods of magmatic quiescence. This contrasts with dominantly stagnant-lid-like signatures for most Barberton Hadean zircons. The diverse settings for Jack Hills and Barberton detrital zircons imply contemporaneous operation of different tectonic styles during the Hadean, as well as a broader diversity of early crustal origins than previously known.